Development of the Sensory–Motor Dysfunction Questionnaire and Pilot Reliability Testing - Ambalavanar, Ushani; Haavik, Heidi; Rotondi, Nooshin Khobzi; Murphy, Bernadette Ann (Brain sciences, 2024)
Both chronic and recurrent spinal pain alter sensorimotor integration (SMI), which is demonstrated using complex neurophysiological techniques. Currently, there is no patient-reported outcome measure that documents and/or assesses SMI in populations with spinal problems. The purpose of this study was to develop the Sensory–Motor Dysfunction Questionnaire (SMD-Q) and assess its test–retest reliability and internal consistency in individuals with recurrent spinal pain. The SMD-Q was developed based on the existing literature on motor control disturbances associated with disordered SMI. The initial SMD-Q drafts underwent review by two separate panels of subject matter experts and a focus group with subclinical spine pain. Their suggestions were incorporated into the questionnaire prior to reliability testing. The questionnaire was administered twice at a seven-day interval using QualtricsTM. A total of 20 participants (14 females and 6 males; 20.95 ± 2.46 years of age) completed the study. Quadratic weighted kappa (Kw) was used to assess test–retest reliability and Cronbach’s alpha (α) was used to assess internal consistency. Four items had a Kw < 0.40, seven had a 0.40 < Kw < 0.75, and one had a Kw > 0.75 (excellent agreement), with excellent internal consistency (α > 0.90). The pilot SMD-Q appears to reliably measure altered SMI, suggesting that revisions and testing with a larger sample are worth pursuing.